The largest minority population in the U.S. without adequate dental care. (July 2017) - Waldman, H. Barry; Perlman, Steven P.; Wong, Allen
ABSTRACT: A recent series of reports in Health Affairs reviewed the disparities in securing needed oral health services in the U.S. Despite an extensive oversight of the many issues involved, no direct mention is made of the particular conditions of the largest minority population in the U.S. unable to access dental care—the tens of millions of individuals with special health care needs. A review is provided of the particular barriers and conditions faced by this increasing population in its efforts to secure needed services.